Work-Life Balance: Essential or Ephemeral? - Stephania A. Cormier (Frontiers Research Topics, 2017)
Burn-out and suicide rates among physicians and scientists in academic medicine are at an all-time high and jeopardize the future of our entire profession. In the last 4 years alone, burn-out rates among physicians have increased by 25%. In a recent 2017 Medscape publication, burn-out rates in Critical Care physicians ranked in 9th place and Pediatricians ranked 13th among 27 subspecialties. Astonishingly, over 50% of the participants reported burn-out symptoms, with clear race and gender disparities. While men generally report higher burn-out rates than women, it is important to emphasize that response rates from women in these surveys were notoriously low and may not represent the complete picture. These numbers are even more dismal for tenured academic faculty at research-extensive universities. In this group, emotional exhaustion (i.e. high burn-out) is reported at 35% with a clear association with age and lower burn-out levels in the older tenured faculty. While no gender or racial/ethnic differences were found in this particular group, higher levels of burn-out were identified in individuals with financial responsibilities beyond a spouse and child. While it is comforting to note the increasing public interest and research activities in this field, successful approaches to ameliorate the burden and consequences of physician burn-out are still inadequately developed. Academic centers increasingly offer some type of work-life balance program to their employees but, unfortunately, these programs are frequently adopted from corporate business models and remain largely ineffective in the academic environment. It should be evident to most administrators that the stressors of academic clinicians and scientists substantially differ from those of corporate employees. Based on these observations and over 75 years of combined experience in academic medicine amongst the three editors of this Research Topic, we collected 26 manuscripts from 22 authors at different career stages and different genders, ethnicities, marital status and subspecialties to identify and stratify common and specific stressors and therapeutic approaches to ameliorate burn-out and achieve work-life balance in academic medicine. We are confident that each reader will identify with at least one, if not several, of the authors' opinions, experiences and approaches to attain greater work-life balance and thereby avoid the consequences of burn-out in modern academic medicine.